(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Distance learning using digital technologies has become a vital necessity in Ukraine in the context of pandemic and war. Such a transition took place in a short period of time and has now become a significant innovation in the educational space of Ukraine. Foreign experience in implementing distance learning has been analyzed, which allows taking into account the individual abilities, needs, temperament, and employment of students who have the opportunity to master the educational program in any sequence and pace, and interact with participants in the educational process through the use of distance learning platforms. The principles of open education are outlined (mobility of students and teachers; equal access to educational systems; ensuring quality education; structuring and implementation of educational services). The characteristics of blended learning models that are actively implemented in foreign and domestic educational institutions (Rotation Model, Flex Model, A La Carte Model, Enriched Virtual Model) are presented. The didactic capabilities of the main distance learning platforms (Moodle, Edmodo, iSpring, WebTutor, Google Classroom) are revealed. The interconnected structural elements of distance learning platforms in a blended learning environment are summarized and graphically presented. The features of the practical application of distance learning platforms in blended learning at the Mykhailo Kotsiubynskyi Vinnytsia State Pedagogical University are analyzed according to its main components in the process of professional training of education seekers in the specialties 015.39 Professional Education (Digital Technologies), 011 Educational and Pedagogical Sciences, 073 Management. The results of a survey of education seekers and teachers are presented. in order to assess the effectiveness of the use of distance learning technology in studying educational material, organizing independent work, communication and interaction of all participants in the educational process. The main platforms for providing distance learning at the university are described and graphically presented, the main criteria for selecting distance learning sites by scientific and pedagogical workers, types of static data when working with distance platforms, types of activities of participants in the educational process using distance learning platforms, types of reproduction of the results of education seekers using distance learning platforms. The main aspects of the practical experience of implementing blended learning in professional training of specialists at the pedagogical university are summarized. The main directions of innovative approaches to the use and implementation of structural elements remote platforms in the conditions of blended learning in the process of professional training of specialists are determined, namely: access to educational content: interaction with the teacher; interaction between students; evaluation and feedback.